Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2196/31461
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of and Satisfaction With Artificial Intelligence in Cancer Treatment: A Clinical Decision Support System Experience and Implications for Low-Middle–Income Countries

Abstract: As technology continues to improve, health care systems have the opportunity to use a variety of innovative tools for decision-making, including artificial intelligence (AI) applications. However, there has been little research on the feasibility and efficacy of integrating AI systems into real-world clinical practice, especially from the perspectives of clinicians who use such tools. In this paper, we review physicians’ perceptions of and satisfaction with an AI tool, Watson for Oncology, which is used for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…With regard to desirable features of AI-enabled CDSSs, a unique theme from the interviews with Indian physicians was the tool's ability to provide an antibiotic of choice after weighing the cost of medicines with the socioeconomic situation of the patient. A recent study about physicians’ perceptions on the use of an AI-enabled CDSS for oncology across India, China, Brazil, South Korea, and Mexico also reported cost consideration as a desirable feature [28] . This theme relates to the local context of poverty and out-of-pocket expenditure for medicines in India which is vastly different from the context in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to desirable features of AI-enabled CDSSs, a unique theme from the interviews with Indian physicians was the tool's ability to provide an antibiotic of choice after weighing the cost of medicines with the socioeconomic situation of the patient. A recent study about physicians’ perceptions on the use of an AI-enabled CDSS for oncology across India, China, Brazil, South Korea, and Mexico also reported cost consideration as a desirable feature [28] . This theme relates to the local context of poverty and out-of-pocket expenditure for medicines in India which is vastly different from the context in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples of localization-related challenges have been reported in studies conducted in countries such as Mexico and China, 41,47 and our recently published review includes additional examples. 48 Prior studies have also demonstrated how implementation and the use of AI-based tools in resource-poor countries require a strong understanding of local social contexts, infrastructure requirements, and availability of other resources. 21,49 In particular, there is an important need to assess the role of local social and cultural context in training an AI tool that has been developed in a Western setting.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing vast datasets of medical literature, clinical trial data, and patient records, Watson for Oncology provides evidence-based treatment recommendations, enhancing the precision and efficacy of cancer care. In finance, JPMorgan Chase provides a notable example of successful AI implementation (Emani et al, 2022;Kann et al, 2021). The bank employs machine learning algorithms to analyse customer data, detect patterns of fraudulent activities, and enhance cybersecurity.…”
Section: Drivers Of Ai In the Fourth Industrial Revolution (4ir)mentioning
confidence: 99%